A importância do fluxo de caixa e a sua utilização para a gestão financeira de uma empresa de pequeno porte. Estudo de caso: Mercado Beckbem - LIMA, Celso Freitas de; CUDIGNOTO, Felipe Evangelista; SOARES, Fernanda da Silva; MARQUES, Kelvin de Oliveira Souza; FERREIRA, Letícia; DANTAS, Marcos Vinicius de Brito; SENA, Vanessa Medeiros de (172, 2016)
A finalidade desta monografia é demonstrar a importância do fluxo de caixa como uma ferramenta fundamental para o desenvolvimento das empresas de pequeno porte utilizando como estudo de caso o mercadinho BECKBEM que trabalha na área de comércio de alimentos. Sem a utilização desta ferramenta nas empresas se torna quase impossível uma organização financeira eficaz, deixando as informações destorcidas e totalmente desorganizadas, não se tendo assim noção dos reais resultados da empresa. Ao decorrer do trabalho foi utilizado como método de abordagem o hipotético dedutivo que visa construir e testar uma possível solução para um determinado problema e como pesquisa prática o estudo de caso. O objetivo do mesmo é mostrar a importância da demonstração de fluxo de caixa para as pequenas empresas e como essa ferramenta pode mudar toda a vida financeira da empresa, verificando com eficiência suas entradas e saídas, identificar os recursos disponíveis na organização e até mesmo verificar através do fluxo de caixa se a empresa está estável financeiramente ou não, para a construção de projetos futuros. Concluise que o mercadinho BECKBEM, a empresa em estudo necessita da demonstração de fluxo de caixa, pela falta de organização das finanças. Para que se tenha o total controle de tudo o que entra e sai da empresa, cálculo e interpretação para se prevenir das necessidades ou oportunidades futuras, e também se ter as informações corretas do estado financeiro da empresa.

The purpose of this monograph is to demonstrate the importance of cash flow as a fundamental tool for the development of small businesses using as a case study the shop BECKBEM who works in the area of food trade. Without the use of this tool in companies becomes almost impossible a financial organization effective, leaving the information distorted and completely disorganized, not having any notion the real results of the company. The course of the work was used as a method of the hypothetical deductive approach which aims to build and test a possible solution to a particular problem and how the practice research case study. The goal of it is to show the importance of the Statement of cash flow for small businesses and how this tool can change the entire financial life of the company, effectively checking their inputs and outputs, identify the resources available in the Organization and even check through cash flow if the company is financially stable or not, for the construction of future projects. It is concluded that the store BECKBEM, the company under study requires the demonstration of cash flow, the lack of the finance organization. To have full control of everything that goes in and out of the enterprise, calculation and interpretation prevent the needs or future opportunities, and also have the correct information of the financial state of the company.

The purpose of this monograph is to demonstrate the importance of cash flow as a fundamental tool for the development of small businesses using as a case study the shop BECKBEM who works in the area of food trade. Without the use of this tool in companies becomes almost impossible a financial organization effective, leaving the information distorted and completely disorganized, not having any notion the real results of the company. The course of the work was used as a method of the hypothetical deductive approach which aims to build and test a possible solution to a particular problem and how the practice research case study. The goal of it is to show the importance of the Statement of cash flow for small businesses and how this tool can change the entire financial life of the company, effectively checking their inputs and outputs, identify the resources available in the Organization and even check through cash flow if the company is financially stable or not, for the construction of future projects. It is concluded that the store BECKBEM, the company under study requires the demonstration of cash flow, the lack of the finance organization. To have full control of everything that goes in and out of the enterprise, calculation and interpretation prevent the needs or future opportunities, and also have the correct information of the financial state of the company.
Keywords: Fluxo de caixa; Gestão e Negócios